Digital droplet PCR analysis of organoids generated from mouse mammary tumors demonstrates proof-of-concept capture of tumor heterogeneity - Lake, Katherine E.; Colonnetta, Megan M.; Smith, Clayton A.; Saunders, Kaitlyn; Martinez-Algarin, Kenneth; Mohta, Sakshi; Pena, Jacob; McArthur, Heather L.; Reddy, Sangeetha M.; Roussos Torres, Evanthia T.; Chen, Elizabeth H.; Chan, Isaac S. (Frontiers in Cell and Developmental Biology, 2024)
Breast cancer metastases exhibit many different genetic alterations, including copy number amplifications (CNA). CNA are genetic alterations that are increasingly becoming relevant to breast oncology clinical practice. Here we identify CNA in metastatic breast tumor samples using publicly available datasets and characterize their expression and function using a metastatic mouse model of breast cancer. Our findings demonstrate that our organoid generation can be implemented to study clinically relevant features that reflect the genetic heterogeneity of individual tumors.